Hubungan Kontrol Diri dengan Perilaku Membolos Siswa - Putri, Megawati Silvia; Daharnis, Daharnis; Zikra, Zikra (Konselor, 2017)
The purpose of this research to describe self control and truant behavior students and examine the relationship between self control with the behavior of truant students. This research applied quantitative method and descriptive correlational design, with a sample of 234 students,  that drawn by Propotional Stratified Random Sampling technique. The instrument of this research was a scale of Likert model. Hypothesis testing of research using the formula Pearson Product Moment Correlation with SPSS for mindows release 20.00. The results showed: (1) on average,  the truant behavior of class X and XI SMA Negeri 7 Padang was 19.86 hours of lessons in 2 months, (2) on average,  class X and XI SMA Negeri 7 Padang self control was 108.24 at the high category, (3) there was significant negative of self-control with truant behavior of students, with a correlation coefficient -0.289  significance level 0.000, which is smaller than 0.05. This research can be used as an analysis of the needs of students for the teacher of guidance and counseling for the manufacture of guidance and counseling services programs at SMA Negeri 7 Padang.